Fused‐Ring Formation by an Intramolecular "Cut‐and‐Sew" Reaction between Cyclobutanones and Alkynes. (6th February 2018) - Deng, Lin; Jin, Likun; Dong, Guangbin
Abstract: The development of a catalytic intramolecular "cut‐and‐sew" transformation between cyclobutanones and alkynes to construct cyclohexenone‐fused rings is described herein. The challenge arises from the need for selective coupling at the more sterically hindered proximal position, and can be addressed by using an electron‐rich, but less bulky, phosphine ligand. The control experiment and 13 C‐labelling study suggest that the reaction may start with cleavage of the less hindered distal C−C bond of cyclobutanones, followed by decarbonylation and CO reinsertion to enable Rh insertion at the more hindered proximal position.